Convenient preparation of high molecular weight poly(dimethylsiloxane) using thermally latent NHC-catalysis: a structure-activity correlation - Naumann, Stefan; Klein, Johannes; Wang, Dongren; Buchmeiser, Michael R. (Beilstein Journal of Organic Chemistry, 2015)
The polymerization of octamethylcyclotetrasiloxane (D4) is investigated using several five-, six- and seven-membered N-heterocyclic carbenes (NHCs). The catalysts are delivered in situ from thermally susceptible CO2 adducts. It is demonstrated that the polymerization can be triggered from a latent state by mild heating, using the highly nucleophilic 1,3,4,5-tetramethylimidazol-2-ylidene as organocatalyst. This way, high molecular weight PDMS is prepared (up to >400 000 g/mol, 1.6 < ÐM < 2.5) in yields >95%, using low catalyst loadings (0.2–0.1 mol %). Furthermore, the results suggest that a nucleophilic, zwitterionic mechanism is in operation, in preference to purely anionic polymerization.
Keywords: latency; N-heterocyclic carbenes; ring-opening organocatalysis; polymerization; polysiloxanes

(untitled) - Hahn, F. E.; Jahnke, M. C. (Angew. Chem., Int. Ed., 2008)

(untitled) - Dröge, T.; Glorius, F. (Angew. Chem., Int. Ed., 2010)

(untitled) - Hopkinson, M. N.; Richter, C.; Schedler, M.; Glorius, F. (Nature, 2014)

(untitled) - Kiesewetter, M. K.; Shin, E. J.; Hedrick, J. L.; Waymouth, R. M. (Macromolecules, 2010)

(untitled) - Dove, A. P. (ACS Macro Lett., 2012)

(untitled) - Fèvre, M.; Pinaud, J.; Gnanou, Y.; Vignolle, J.; Taton, D. (Chem. Soc. Rev., 2013)

(untitled) - Naumann, S.; Dove, A. P. (Polym. Chem., 2015)

(untitled) - Naumann, S.; Epple, S.; Bonten, C.; Buchmeiser, M. R. (ACS Macro Lett., 2013)

(untitled) - Naumann, S.; Schmidt, F. G.; Speiser, M.; Böhl, M.; Epple, S.; Bonten, C.; Buchmeiser, M. R. (Macromolecules, 2013)

(untitled) - Raynaud, J.; Absalon, C.; Gnanou, Y.; Taton, D. (J. Am. Chem. Soc., 2009)

(untitled) - Bantu, B.; Pawar, G. M.; Decker, U.; Wurst, K.; Schmidt, A. M.; Buchmeiser, M. R. (Chem. – Eur. J., 2009)

(untitled) - Coutelier, O.; El Ezzi, M.; Destarac, M.; Bonnette, F.; Kato, T.; Baceiredo, A.; Sivasankarapillai, G.; Gnanou, Y.; Taton, D. (Polym. Chem., 2012)

(untitled) - Scholten, M. D.; Hedrick, J. L.; Waymouth, R. M. (Macromolecules, 2008)

(untitled) - Raynaud, J.; Ciolino, A.; Baceiredo, A.; Destarac, M.; Bonnette, F.; Kato, T.; Gnanou, Y.; Taton, D. (Angew. Chem., Int. Ed., 2008)

(untitled) - Zhang, Y.; Chen, E. Y.-X. (Angew. Chem., Int. Ed., 2012)

(untitled) - Hong, M.; Chen, E. Y.-X. (Angew. Chem., Int. Ed., 2014)

(untitled) - Naumann, S.; Schmidt, F. G.; Schowner, R.; Frey, W.; Buchmeiser, M. R. (Polym. Chem., 2013)

(untitled) - Matsuoka, S.-i.; Namera, S.; Suzuki, M. (Polym. Chem., 2015)

(untitled) - Manners, I. (Angew. Chem., Int. Ed. Engl., 1996)

(untitled) - Chojnowski, J. (J. Inorg. Organomet. Polym., 1991)

The polysiloxanes - Mark, J. E.; Schaefer, D. W.; Lin, G. (Oxford University Press, 2015)

(untitled) - Lohmeijer, B. G. G.; Dubois, G.; Leibfarth, F.; Pratt, R. C.; Nederberg, F.; Nelson, A.; Waymouth, R. M.; Wade, C.; Hedrick, J. L. (Org. Lett., 2006)

(untitled) - Brown, H. A.; Chang, Y. A.; Waymouth, R. M. (J. Am. Chem. Soc., 2013)

(untitled) - Rodriguez, M.; Marrot, S.; Kato, T.; Stérin, S.; Fleury, E.; Baceiredo, A. (J. Organomet. Chem., 2007)

(untitled) - Marrot, S.; Bonnette, F.; Kato, T.; Saint-Jalmes, L.; Fleury, E.; Baceiredo, A. (J. Organomet. Chem., 2008)

(untitled) - Naumann, S.; Buchmeiser, M. R. (Catal. Sci. Technol., 2014)

(untitled) - Van Ausdall, B. R.; Glass, J. L.; Wiggins, K. M.; Aarif, A. M.; Louie, J. (J. Org. Chem., 2009)

(untitled) - Higgins, E. M.; Sherwood, J. A.; Lindsay, A. G.; Armstrong, J.; Massey, R. S.; Alder, R. W.; O'Donoghue, A. C. (Chem. Commun., 2011)

(untitled) - Magill, A. M.; Cavell, K. J.; Yates, B. F. (J. Am. Chem. Soc., 2004)

(untitled) - Kim, Y.-J.; Streitwieser, A. (J. Am. Chem. Soc., 2002)

Organic chemistry - Brown, W. H.; Foote, C. S.; Iverson, B. L.; Anslyn, E. V. (Brooks/Cole, Cengage Learning, 2012)

(untitled) - Chandrasekhar, V.; Boomishankar, R.; Nagendran, S. (Chem. Rev., 2004)

(untitled) - Brown, H. A.; Waymouth, R. M. (Acc. Chem. Res., 2013)

Principles of Polymerization - Odian, G. (John Wiley & Sons, 2004)